Colloidal Crystals: Transferable Crack‐Free Colloidal Crystals on an Elastomeric Matrix with Surface Relief (Adv. Funct. Mater. 46/2013). (10th December 2013) - Kim, Mi Ri; Im, Sang Hyuk; Kim, Young‐Seok; Cho, Kuk Young
<x xml:space="preserve">Abstract</x> Y.‐S. Kim, K. Y. Cho, and co‐workers fabricate crackfree 3D silica colloidal assemblies on elastomeric polydimethylsiloxane stamps using a lift‐up method. On page 5700, surface relief structures on the substrate enable the formation of the assemblies. Control over the lift‐up rate and colloid suspension concentration result in 10 μm thick (height of surface relief) flat colloidal assemblies. This strategy not only provides a means to assemble crack‐free colloidal crystals on a soft hydrophobic surface, but also enables transfer of the crack‐free colloidal crystals onto a curved surface. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>